1992
DOI: 10.5271/sjweh.1571
|View full text |Cite
|
Sign up to set email alerts
|

Knee disorders in carpet and floor layers and painters.

Abstract: KIVIMA.KI J, RIIHIMAKI H, HA.NNINEN K. Knee disorders in carpet and floor layers and painters. Scand J Work Environ Health 1992;18:310-6. In an evaluation of the effect of kneeling work on the knees, 168 actively working carpet and floor layers and 146 house painters were examined with the aid of a questionnaire, a clinical examination, and radiography. Reported knee pain, knee accidents, and treatment regimens for the knees were more common among the carpet and floor layers than among the painters. Radiograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
0
19

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(113 citation statements)
references
References 11 publications
4
89
0
19
Order By: Relevance
“…Kivimaki et a1 (4) found no difference in the frequency of severe knee osteoarthritis among 25-to-49-year-old floorlayers compared with painters, a finding in accordance with our results. Studies from the 1950s showed an increased prevalence of radiological knee osteoarthritis in miners when they were compared with different reference groups without kneeling or squatting work (1,7).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Kivimaki et a1 (4) found no difference in the frequency of severe knee osteoarthritis among 25-to-49-year-old floorlayers compared with painters, a finding in accordance with our results. Studies from the 1950s showed an increased prevalence of radiological knee osteoarthritis in miners when they were compared with different reference groups without kneeling or squatting work (1,7).…”
Section: Discussionsupporting
confidence: 93%
“…A study of floorlayers, including a quantitative description of kneestraining work, was negative, but this study included only subjects below 50 years of age (4).…”
mentioning
confidence: 99%
“…These include two cohort studies, 21,33 five case-control studies, 11,13,37,40,44 and five cross-sectional studies. 17,18,23,28,42 Nine studies reported a positive relationship between knee OA and occupation (OR ¼ 1.4-4.7), 11,13,17,21,23,37,40,44 but only three scored high on methodological quality. 13,37,40 Many studies in this subgroup are older and have procedural flaws, such as failing to control for relevant covariates 17,21 or low participation rates.…”
Section: Occupational Groupsmentioning
confidence: 99%
“…[17][18][19]23,28,39,43 Twenty studies found a statistically significant relationship between occupational physical loading and knee OA (OR ¼ 1.4-7.9); of these, 13 received high quality scores. 9,13,14,19,25,26,29,31,34,37,39,40,43 All three cohort studies reported significant results for men.…”
Section: Occupational Physical Loading By Sexmentioning
confidence: 99%
“…Vingård et al [9] found greater risk among male construction workers than other occupational groups. Carpet and floor layers had increased risk of patellar osteophytes, but not tibiofemoral joint degeneration, compared with a reference group of house painters [10]. In a separate investigation conducted by Kirkeskov Jensen et al [11], both carpenters and floor layers, especially those over 50 years of age, had higher prevalence of radiologic OA compared with compositors (seated layout work on video display units).…”
Section: Introductionmentioning
confidence: 97%